Nature-Inspired Nanocomposites for Toxic Heavy Metals Removal: An Overview - Mudassar SanaUllah; Awais Ali Aslam; Abhishek Thakur; Sania Amjad; Shahzaib Ishfaq; Sadaf Ul Hassan; Usman Haidar; Muhammad Shahid Nazir; Mahmood Ahmed; Marek Kowalczuk (Reviews of Environmental Contamination and Toxicology, 2026)

Leaf pigment profiling for sensitive detection of nutrient deficiency syndromes in strawberry - Muhammad Ishfaq; Bastian Leander Franzisky; Guillaume Gomard; Susanne Baldermann; Christoph-Martin Geilfus (Computers and Electronics in Agriculture, 2026)

Microplastic–cadmium co-contamination in agricultural soils: A critical review of interactions, transfer, and plant exposure - Longcheng Li; Letian Wang; Muhammad Ishfaq; Kai Zhang; Xuejun Liu; Jianlin Shen; Zhenhua Zhang; Matthias C. Rillig (Critical Reviews in Environmental Science and Technology, 2026)

Maize Hybrids Show Differential Response to Glutamine Application At the Physiological Level - Mahmood Ul Hassan; Chandni Iqbal; Andrew Nasa Thompson; Muhammad Ishfaq; Lianlian Liu; Qingling Zhao; Xuexian Li (Journal of Soil Science and Plant Nutrition, 2026)

Long-Term Fermented Chicken Manure (CM) Amendment Enhances Soil Health, Sugar Beet Yield, and Shifts Microbial Functional Diversity - Jianyu Zhang; Songlin Yang; Xiaochen Lin; Shafaque Sehar; Muhammad Ishfaq; Muhammad Riaz; Muhammad Faheem Adil; Saqib Bilal; Xiaoyu Zhao; Jean Wan Hong Yong; Baiquan Song (Sugar Tech, 2026)

Amino acid-chelated zinc application enhances sugar beet growth performance in carbonate alkaline soil by optimizing rhizosphere zinc speciation and microbial community structure - Jianyu Zhang; Chuanhe Zhao; Yunlong Guo; Muhammad Ishfaq; Songlin Yang; Wenya Wang; Qiue Jia; Shangxuan Liu; Yan Wang; Wang Xing; Baiquan Song (Applied Soil Ecology, 2026)

Nanoparticles in potato disease management: Applications, mechanisms, and future perspectives for sustainable crop production - Aneeza Ishfaq; Ishrat Bano; Irfan Haidri; Muhammad Shahid; Muhammad Sohail Akram; Muhammad Khubeb Ashfaq; Sabir Hussain; Tanvir Shahzad; Faisal Mahmood (Physiological and Molecular Plant Pathology, 2026)

Precision root zone fertilization reconciles productivity and nitrogen efficiency in intensive wheat systems - Solomon Yokamo; Bin Wang; Muhammad Ishfaq; Muhammad Irfan; Yiliu Wang; Dianjun Lu; Xiaoqin Chen; Huoyan Wang (Field Crops Research, 2026)

Heat-Wave Prediction via Joint Regression and Classification with a Bayesian Deep Bidirectional LSTM Model - Iqra Sardar; Farzana Noor; Muhammad Javed Iqbal; Ishfaq Ahmad; Muhammad Azeem Akbar (Environmental Modelling & Software, 2026)

Antibacterial flavonoid derivatives: in silico ADMET, DFT, Molecular Docking, MD Simulation and in vitro verification - Atif Ishfaq; Affifa Tajammal; Riaz Maira; Aisha Waheed Qureshi; Babar Aleeza; Muhammad Asim Raza Basra (In Silico Pharmacology, 2026)

Microplastics as Trojan horses: Vectors of pathogens, pollutants, and antimicrobial resistance genes - Ghazala Saeed; Ali Afzal; Afzal Nimra; Zaira Ahmad; Amna Rehman; Kaleem Maqsood; Tayyba Jan; Muhammad Ishfaq Ahmad; Naveed Karim; Byong-Hun Jeon; Ghulam Mustafa; Fakhar Zaman; et al. (Environmental Research, 2026)

Machine learning-assisted meta-analysis reveals melatonin crosstalk regulating plant growth plasticity under heavy metal stress - Muhammad Moeen-ud-din; Muhammad Azher Hassan; Ambreen Ahmad; Liu Xianhua; Muhammad Ishfaq; Muhammad Irfan; Yujiang Li; Liu Yang; Liu Chunguang (Plant Cell Reports, 2026)

Mechanistic Insights into Silicon-Induced Modulation of Morphophysiological Traits and Plant Defense System in Mung Bean (Vigna Radiata L.) under Drought Stress - Mazhar Abbas; Ejaz Ahmad Waraich; Muhammad Ahmad; Nazia Ishfaq; Arslan Haider; Tahrim Ramzan; Muhammad Nazim; Usman Zulfiqar; Muhammad Faisal Maqsood; Abdul Rehman; Waleed A. A. Alsakkaf; Hayssam M. Ali (Journal of Soil Science and Plant Nutrition, 2026)

Structural equation modelling for sustainable land management: Assessing ridge-furrow rainwater harvesting and chopped straw effects on soil moisture dynamics and sainfoin yield in semi-arid slopes - Ibrahim Awuku; Abdul Qadeer; Xiaole Zhao; Rizwan Azim; Qi Wang; Wen Ma; Fujia Li; Muhammad Ishfaq; Xuchun Li; Bing Liu (Computers and Electronics in Agriculture, 2026)

Molecular Characterization of Oculocutaneous Albinism in Consanguineous Pakistani Families: Unraveling Disease-Causing Pathogenic Variants in OCA2 and TYR Genes for Precision Diagnosis - Haiba Kaul; Shagufta Naz; Hafiz Ishfaq Ahmad; Nameerah Saleem; Muhammad Shakil; Sabika Firasat; Bilal Majeed; Saima Sharif; Farzana Rashid; Abdullah Etezaz; Muhammad Umer Khan (Biochemical Genetics, 2026)

Molecular and functional insights of β-1,3-glucan-binding protein (β-GBP) in polyphenol-based oxidative stress mitigation in whiteleg shrimp (Penaeus vannamei) - Muhammad Safdar; Safdar Imran; Hafiz Ishfaq Ahmad; Mehmet Ozaslan; Xia Wang; Xiuli Chen (Aquaculture, 2026)

Phosphogenesis of Kakul Garlaniyan phosphorites during the early Cambrian in northeastern Pakistan - Massam Ali; Haifeng Fan; Danish Khan; Fang Zhang; Ishfaq Ahmad; Muhammad Asif Sherliyat; Yuhan Ma; Jibran Hussain; Hanjie Wen (Journal of Asian Earth Sciences, 2026)

Data augmentation and normalization strategies for improving satellite image segmentation - Ayesha Saadia; Muhammad Ishfaq; Muhammad Umair; Iqbal Murtza; Munahil Yaqoob (Earth Science Informatics, 2026)

Agricultural and socio-ecological benefits of reducing chemical nitrogen fertilizer and using organic amendments: a sugar beet case study in China's black soil region - Yunlong Guo; Xiaochen Lin; Muhammad Faheem Adil; Muhammad Ishfaq; Muhammad Riaz; Shafaque Sehar; Songlin Yang; Yan Wang; Zhishan Yan; Baiquan Song (Applied Soil Ecology, 2026)

Optimizing wheat fertilizer placement through lateral distance and row configuration for enhanced yield, profitability, and nitrogen use efficiency - Solomon Yokamo; Bin Wang; Muhammad Irfan; Yiliu Wang; Muhammad Ishfaq; Dianjun Lu; Xiaoqin Chen; Xiaoqi Jin; Huoyan Wang (Plant and Soil, 2026)

Biochar remodeled rhizosphere microbial community structure and function to alleviate sugar beet under fomesafen phytotoxicity - Yunlong Guo; Xiaochen Lin; Baiquan Song; Chuanhe Zhao; Muhammad Riaz; Muhammad Ishfaq (Journal of Environmental Management, 2025)

Engineering stable gels: Whey protein isolate microgel-induced complexation with β-cyclodextrin in high internal phase emulsion gel - Akhunzada Bilawal; Muhammad Ishfaq; Shah Zareen; Zhanmei Jiang; Juncai Hou (Food Hydrocolloids, 2025)

Biochar Amendment Improved Growth and Yield of Fragrant Rice and Reduced Arsenic (As) Accumulation under As-contaminated Irrigation Water - Umair Ashraf; Talat Mansha; Shakeel Ahmad Anjum; James DeDecker; Abrar Hussain; Fahd Rasul; Muhmmad Abrar; Muhammad Ishfaq (Water, Air, & Soil Pollution, 2025)

Aflatoxin B1-Induced male reproductive Toxicity: Bioactivation, mechanisms, molecular pathways, and Mitigation by phytochemicals in humans and animals - Zemin Zhu; Muhammad Shahab; Shahab Uddin; Imdadullah; Muhammad Ishfaq (Toxicon, 2025)

Harnessing metal-organic frameworks (MOFs) in agriculture: Mechanisms and application strategies for management of plant diseases - Aneeza Ishfaq; Muhammad Shahid; Sabir Hussain; Tanvir Shahzad; Yumna Rasheed; Faizah Amer Altihani; Mohamed Hashem; Faisal Mahmood (Physiological and Molecular Plant Pathology, 2025)

Understanding flood behavior in the Kashmir Himalayas through copula-driven models - Ishfaq Gujree; Shafique ur Rehman; Joshal K. Bansal; Ningsheng Chen; Aijaz Ahmad Reshi; M. Sultan Bhat; Muhammad Atiq Ur Rehman Tariq (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Lipid droplet-organelle communication: A new perspective on AFB1-induced lipotoxicity in chicken hepatocytes and the protective effect of curcumin - Sihong Li; Jun Jiang; Qian Wu; Muhammad Ishfaq; Jiaqing Cheng; Lu Liu; Dong Niu (Food Bioscience, 2025)

Airborne microplastics in leaves and food safety risks - Muhammad Ishfaq; Noman Shakoor; Matthias C. Rillig; Christoph-Martin Geilfus (Trends in Plant Science, 2025)

Amino acid-modified nano-magnetite boosts okra [Abelmoschus esculentus (L.) Moench] yield and iron enrichment for improved nutrition - Maham Ishfaq; Fahad Shafiq; Sumera Anwar; Muhammad Iqbal; Syed Hammad Raza; Arslan Mahmood; Muhammad Ashraf (BioMetals, 2025)

Optimization of nitrogen fertilizer application enhanced sugar beet productivity and socio-ecological benefits in China: A meta-analysis - Longfeng Wang; Baiquan Song; Muhammad Ishfaq; Xiaoyu Zhao (Soil and Tillage Research, 2025)

Reducing Phosphorus Fertilizer Application in the Typical Pomelo Production Region of China Improves Fruit Quality Traits via Metabolic Reprogramming - Huilan Luo; Muhammad Ishfaq; Minwen Yan; Jing Zhang; Siwen Zhang; Xue Zhang; Ling Tong; Mahmood Ul Hassan; Haifang Liao; Jiuliang Xu; Delian Ye; Liangquan Wu; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Microbial Synthesis of ZnO Nanoparticles: A Green Strategy for Mitigating Wastewater Stress in Wheat (Triticum aestivum) - Aneeza Ishfaq; Irfan Haidri; Usman Shafqat; Imran Khan; Hafiz Muhammad Rizwan; Muhammed Umair Hassan; Muhammad Irfan; Muhammad Adnan; Faisal Mahmood (Water, Air, & Soil Pollution, 2025)

Transcriptome profiling of tomato fruit ripening and postharvest quality response to magnesium deficiency stress - Muhammad Ishfaq; Yongqi Wang; Muhammad Azher Nawaz; Haichao Zhou; Xuexian Li (Plant and Soil, 2025)

Comprehensive assessment of the agronomic, environmental and economic benefits of localized fertilizer placement in China's intensive cereal production systems - Solomon Yokamo; Bin Wang; Muhammad Ishfaq; Weiwei Huan; Muhammad Irfan; Yiliu Wang; Jackson Nkoh Nkoh; Dianjun Lu; Xiaoqin Chen; Huoyan Wang (Agricultural Systems, 2025)

Nitrogen-phosphorus conservation and trade-offs in mangroves - Muhammad Ishfaq; Nora Fung-Yee Tam; Tao Lang; Muzammil Hussain; Haichao Zhou (Plant and Soil, 2025)

Mercury-induced alterations in soil microbiome: A potential for microbiome stewardship to remediate contaminated soils - Tao Lang; Muzammil Hussain; Muhammad Ishfaq; Noman Shakoor; Nora Fung-Yee Tam; Xiangyi Li; Min Pan; Zhengjie Zhu; Song Xin; Haichao Zhou (Journal of Cleaner Production, 2025)

Corrigendum to “Facile synthesis of CuAl2O4/rGO nanocomposite via the hydrothermal method for supercapacitor applications” [Fuel 357(Part A) (2024) 129688] - Shahzaib Khan; Muhammad Usman; Muhammad Abdullah; Muhammad Suleman Waheed; Muhammad Faheem Ashiq; Muhammad Ishfaq Ahmad; Abdulnasser M. Karami; Muhammad Fahad Ehsan; Sumaira Manzoor; Muhammad Naeem Ashiq (Fuel, 2025)

A Global Perspective on the Biology, Impacts and Management Options of Leptochloa chinensis, a Noxious Weed of Direct-seeded Rice—A Review - Muhammad Ishfaq; Zarina Batool; Usman Zulfiqar; Muhammad Ahmad; Fasih Ullah Haider; Nasim Ahmed; Saddam Hussain; Shakeel Ahmed Anjum; Nadeem Akbar (Journal of Crop Health, 2025)

Impact of biogenic zinc oxide nanoparticles on physiological and biochemical attributes of pea (Pisum sativum L.) under drought stress - Aneeza Ishfaq; Irfan Haidri; Usman Shafqat; Imran Khan; Muhammad Iqbal; Faisal Mahmood; Muhammad Umair Hassan (Physiology and Molecular Biology of Plants, 2025)

Enhancement of Antioxidants’ Enzymatic Activity in the Wheat Crop by Shewanela sp. Mediated Zinc Oxide Nanoparticles Against Heavy Metals Contaminated Wastewater - Irfan Haidri; Aneeza Ishfaq; Muhammad Shahid; Sabir Hussain; Tanvir Shahzad; Usman Shafqat; Sadia Mustafa; Faisal Mahmood (Journal of Soil Science and Plant Nutrition, 2024)

Zinc and methyl jasmonate improve sugar beet tolerance to high boron stress by enhanced leaf photochemical performance - Jialu Huo; Xiaoyu Zhao; Baiquan Song; Muhammad Faheem Adil; Shafaque Sehar; Xilong Liang; Jiaxin Li; Muhammad Ishfaq; Shangxuan Liu; Songlin Yang (Journal of Environmental Management, 2024)

Insights in to iron-based nanoparticles (hematite and magnetite) improving the maize growth (Zea mays L.) and iron nutrition with low environmental impacts - Nauman Yousaf; Muhammad Fahad Sardar; Muhammad Ishfaq; Baogang Yu; Yanting Zhong; Faisal Zaman; Fusuo Zhang; Chunqin Zou (Chemosphere, 2024)

Multinomial classification of NLRP3 inhibitory compounds based on large scale machine learning approaches - Muhammad Ishfaq; Syed Zahid Ali Shah; Ijaz Ahmad; Ziaur Rahman (Molecular Diversity, 2024)

Corrigendum to “Current challenges of hydrothermal treated wastewater (HTWW) for environmental applications and their perspectives: A review” [Environ. Res. 212 Part D (2022) 113532] - Muhammad Usman; Zhijian Shi; Nalok Dutta; Muhammad Awais Ashraf; Bushra Ishfaq; Mohamed Gamal El-Din (Environmental Research, 2024)

Machine learning assisted improved desalination pilot system design and experimentation for the circular economy - Waqar Muhammad Ashraf; Muhammad Ahmad Jamil; Ghulam Moeen Uddin; Bashar Shboul; Kashif Ishfaq; Kim Choon Ng; Mike Dixon; Ben Bin Xu; Muhammad Wakil Shahzad (Journal of Water Process Engineering, 2024)

Towards artificial intelligence empowered performance enhancement of EDM process using nano-graphene mixed bio-dielectric supporting the carbon neutrality and sustainable development - Kashif Ishfaq; Muhammad Asad; Waqar Muhammad Ashraf; Muhammad Sana; Saqib Anwar; Wei Zhang; Vivek Dua (Journal of Cleaner Production, 2024)

Genomic insights into local adaptation of upland cotton in China and Pakistan - Zegang Han; Zhanfeng Si; Mehboob-ur Rahman; Lu He; Yiqian Li; Ali Qaiser Khan; Yun Mao; Sana Zulfiqar; Shumila Ishfaq; Muhammad Mohsan; Muhammad Atif Iqbal; Saba Zafar; et al. (Theoretical and Applied Genetics, 2024)

Climate changes altered the citrus fruit quality: A 9-year case study in China - ZhiHao Dong; MengXin Chen; Anoop Kumar Srivastava; Ul Hassan Mahmood; Muhammad Ishfaq; XiaoJun Shi; YueQiang Zhang; Mohamed G. Moussa; XueXian Li; ChengXiao Hu; FuSuo Zhang (Science of The Total Environment, 2024)

Organic waste-to-bioplastics: Conversion with eco-friendly technologies and approaches for sustainable environment - Zain Ali; Muhammad Abdullah; Muhammad Talha Yasin; Kinza Amanat; Khurshid Ahmad; Ishfaq Ahmed; Muther Mansoor Qaisrani; Jallat Khan (Environmental Research, 2024)

Facile synthesis of CuAl2O4/rGO nanocomposite via the hydrothermal method for supercapacitor applications - Shahzaib Khan; Muhammad Usman; Muhammad Abdullah; Muhammad Suleman Waheed; Muhammad Faheem Ashiq; Muhammad Ishfaq Ahmad; Abdulnasser M. Karami; Muhammad Fahad Ehsan; Sumaira Manzoor; Muhammad Naeem Ashiq (Fuel, 2024)

Foliar Glutamine Application Improves Grain Yield and Nutritional Quality of Field-Grown Maize (Zea mays L.) Hybrid ZD958 - Md Monirul Islam; Mahmood Ul Hassan; Muhammad Ishfaq; Farhana Alam Ripa; Faisal Nadeem; Zeeshan Ahmad; Jiuliang Xu; Peng Ning; Xuexian Li (Journal of Plant Growth Regulation, 2024)

Genotypic variation of tomato to AMF inoculation in improving growth, nutrient uptake, yield, and photosynthetic activity - Fazal Ullah; Habib Ullah; Muhammad Ishfaq; Rahmatullah Khan; Syeda Leeda Gul; Ashrit Gulfraz; Chunwei Wang; Li Zhifang (Symbiosis, 2024)
Arbuscular mycorrhizal fungi (AMF) promote water and mineral nutrients uptake by plant roots, which can reduce the chemical fertilizer inputs in crop production. To gain better insight into the comparative effect of different strains of AMF in improving tomato performance at morphological and physiological levels, seedlings of two tomato cultivars (i.e., Better Boy and Roma) were inoculated with four strains of Glomus mosseae (i.e., HS 1–2 , BEG 12 , BEG 55 , and BEG 54 ) under greenhouse conditions. Results showed that tomato growth and yield varied largely depending on the mycorrhizal strain and tomato cultivar, with wide variations in root colonization ranging from 5.30 to 78.63%. Overall, mycorrhization with BEG 54 showed significantly better tomato performance when compared to the BEG 55, HS 1–2 and BEG 12 strains. In the case of cultivars, Better Boy performed better than Roma cultivar in terms of growth, physiological traits, yield, and fruit quality. The highest plant height, dry matter, nitrogen, phosphorus, potassium, chlorophyll a, chlorophyll b, AMF colonization, yield, fruit juice, ascorbic acid, and titratable acidity contents were recorded in Better Boy cultivar while the highest stem diameter was found in Roma cultivar. Taken together, AMF colonization suggested a promising approach for large-scale tomato production by efficient absorption and utilization of nutrients, and encouraging plants’ symbiotic relationships with soil microorganisms.

Combined Coagulation-Electrocoagulation Treatment of Urban, Peri-urban, and Textile Wastewaters: Process Evaluation and Sludge Setting Characteristics - Suleman Arshad; Waqar Ali Khan; Muhammad Tahir Ishfaq; Muhammad Usman (Water Conservation Science and Engineering, 2023)

Modifying engineered nanomaterials to produce next generation agents for environmental remediation - Muhammad Arslan Ahmad; Muhammad Adeel; Noman Shakoor; Rabia Javed; Muhammad Ishfaq; Yutao Peng; Muhammad Zain; Imran Azeem; Ilyas Ali; Muhammad Usman; Zihao Wu; Gholamreza Gohari; et al. (Science of The Total Environment, 2023)

Sustainable EDM of Inconel 600 in Cu-mixed biodegradable dielectrics: Modelling and optimizing the process by artificial neural network for supporting net-zero from industry - Kashif Ishfaq; Muhammad Sana; Waqar Muhammad Ashraf; Vivek Dua (Journal of Cleaner Production, 2023)

Zinc amendment increases the yield and industrial quality of Beta vulgaris L. cultivated in Northeast China - Xiaoyu Zhao; Baiquan Song; Muhammad Ishfaq; Muhammad Faheem Adil; Milan Kumar Lal; Zhenzhen Wu; Qiue Jia; Wengong Huang (Field Crops Research, 2023)

Development of CuO/CuS/MnO2 ternary nanocomposite for visible light-induced photocatalytic degradation of methylene blue - Muhammad Abdullah; Peter John; Muhammad Naeem Ashiq; Sumaira Manzoor; Muhammad Ishfaq Ghori; Mehar Un Nisa; Abdul Ghafoor Abid; Kashif Younas Butt; Saeed Ahmed (Nanotechnology for Environmental Engineering, 2023)

Corrigendum to “A review of the bioactive ingredients of berries and their applications in curing diseases” [Food Biosci. 44 (2021) 101407] - Akhunzada Bilawal; Muhammad Ishfaq; Munkh-Amgalan Gantumur; Abdul Qayum; Ruijie Shi; Saqib Ali Fazilani; Asif Anwar; Zhanmei Jiang; Juncai Hou (Food Bioscience, 2023)

Insight into potent TLR2 inhibitors for the treatment of disease caused by Mycoplasma pneumoniae based on machine learning approaches - Muhammad Ishfaq; Ziaur Rahman; Muhammad Aamir; Ihsan Ali; Yurong Guan; Zhihua Hu (Molecular Diversity, 2023)

EMS-based mutants are useful for enhancing drought tolerance in spring wheat - Sadaf Zahra; Momina Hussain; Sana Zulfiqar; Shumila Ishfaq; Tayyaba Shaheen; Muhammad Akhtar; Mehboob-ur-Rahman (Cereal Research Communications, 2022)

Effects of Ferula asafetida, closantel, albendazole, oxfendazole, and ivermectin against Haemonchus contortus in goats and sheep - Abdul Jabbar; Muhammad Zahid Iqbal; Muhammad Ashraf; Aneela Zameer Durrani; Hira Sajjad; Mohammed Nasiru Wana; Asad Ullah; Muhammad Imran; Muhammad Shair Zaman Ghauri; Hafiz Ishfaq Ahmad (Tropical Animal Health and Production, 2022)

Growth and productivity assessments of peanut under different irrigation water management practices using CSM-CROPGRO-Peanut model in Eastern Mediterranean of Turkey - Semih Metin Sezen; Ishfaq Ahmad; Muhammad Habib-ur-Rahman; Ebrahim Amiri; Servet Tekin; Kadir Can Oz; Clever Mwika Maambo (Environmental Science and Pollution Research, 2022)
Irrigation water scheduling is crucial to make the most efficient use of ever-decreasing water. As excessive irrigation decreases yield, while imprecise application also causes various environmental issues. Therefore, efficient management of irrigation frequency and irrigation level is necessary to sustain productivity under limited water conditions. The objective of the current study is to assess the water productivity at various irrigation regimes during peanut crop growing seasons (2014 and 2015) in Eastern Mediterranean, Turkey. The field experiments were conducted with treatments consisting of three irrigation frequencies (IF) (IF 1 : 25 mm; IF 2 : 50 mm; and IF 3 : 75 mm of cumulative pan evaporation (CPE)), and four irrigation water levels (WL 1 = 0.50, WL 2 = 0.75, WL 3 = 1.0, and WL 4 = 1.25). WL 1 , WL 2 , WL 3 , and WL 4 treatments received 50, 75, 100, and 125 of cumulative pan evaporation. The CSM-CROPGRO-Peanut model was calibrated with experimental data in 2014 and evaluated with second-year experimental data (2015). The model simulated seed yield and final biomass (dry matter) reasonably well with low normalized root mean square error (RMSE n ) in various irrigation intervals. The model simulated reasonably well for days to anthesis (RMSE = 2.53, d -stat = 0.96, and r 2 = 0.90), days to physiological maturity (RMSE = 2.55), seed yield (RMSE = 1504), and tops biomass dry weight at maturity (RMSE = 3716). Simulation results indicated good agreement between measured and simulated soil water content (SWC) with low RMSE n values (4.0 to 16.8% in 2014 and 4.3 to 18.2% in 2015). Further results showed that IF 2 I 125 irrigation regime produced the highest seed yield. Generally, model evaluation performed reasonably well for all studied parameters with both years’ experimental data. Results also showed that the crop model would be a precision agriculture tool for the extrapolation of the allocation of irrigation water resources and decision management under current and future climate.

Cadmium Toxicity in Plants: Recent Progress on Morpho-physiological Effects and Remediation Strategies - Usman Zulfiqar; Aqsa Ayub; Saddam Hussain; Ejaz Ahmad Waraich; Mohamed A. El-Esawi; Muhammad Ishfaq; Muhammad Ahmad; Nauman Ali; Muhammad Faisal Maqsood (Journal of Soil Science and Plant Nutrition, 2022)

Economic assessment of water-saving irrigation management techniques and continuous flooded irrigation in different rice production systems - Muhammad Ishfaq; Nadeem Akbar; Usman Zulfiqar; Nauman Ali; Fahimuddin Shah; Shakeel Ahmad Anjum; Muhammad Farooq (Paddy and Water Environment, 2022)

Severity of zinc and iron malnutrition linked to low intake through a staple crop: a case study in east-central Pakistan - Muhammad Ishfaq; Abdul Wakeel; Muhammad Nadeem Shahzad; Aysha Kiran; Xuexian Li (Environmental Geochemistry and Health, 2021)

Impact of green trust and green perceived quality on green purchase intentions: a moderation study - Allah Wasaya; Muhammad Abid Saleem; Jamil Ahmad; Muhammad Nazam; M. Mohsin Ali Khan; Mohammad Ishfaq (Environment, Development and Sustainability, 2021)

Foliar Manganese Supply Enhances Crop Productivity, Net Benefits, and Grain Manganese Accumulation in Direct-Seeded and Puddled Transplanted Rice - Usman Zulfiqar; Saddam Hussain; Muhammad Ishfaq; Nauman Ali; Muhammad Umair Yasin; Muhammad Arif Ali (Journal of Plant Growth Regulation, 2021)

Prevention of acetaminophen-induced hepatocyte injury: JNK inhibition and GSTA1 involvement - Yicong Chang; Jingshan He; Bingke Ma; Muhammad Ishfaq; Jiaqi Wang; Ruichen Zhang; Liang Yuan; Jiarui Liu; Changwen Li; Fangping Liu (Molecular & Cellular Toxicology, 2021)

Effects of L-Moments, Maximum Likelihood and Maximum Product of Spacing Estimation Methods in Using Pearson Type-3 Distribution for Modeling Extreme Values - Muhammad Shafeeq ul Rehman Khan; Zamir Hussain; Ishfaq Ahmad (Water Resources Management, 2021)

Influence of Nitrogen Fertilization Pattern on Productivity, Nitrogen Use Efficiencies, and Profitability in Different Rice Production Systems - Muhammad Ishfaq; Nadeem Akbar; Usman Zulfiqar; Nauman Ali; Khawar Jabran; Mohsin Nawaz; Muhammad Farooq (Journal of Soil Science and Plant Nutrition, 2021)

Influence of semi-arid environment on radiation use efficiency and other growth attributes of lentil crop - Muhammad Habib ur Rahman; Ishfaq Ahmad; Depeng Wang; Shah Fahad; Muhammad Afzal; Abdul Ghaffar; Qaisar Saddique; Mehmood Alam Khan; Shah Saud; Shah Hassan; Muhammad Fahad; Mairaj Din; et al. (Environmental Science and Pollution Research, 2021)

Screening of Lipase-Producing Bacteria and Optimization of Lipase-Mediated Biodiesel Production from Jatropha curcas Seed Oil Using Whole Cell Approach - Abdul Haq; Sana Adeel; Alam Khan; Qurrat ul ain Rana; Muhammad Adil Nawaz Khan; Muhammad Rafiq; Muhammad Ishfaq; Samiullah Khan; Aamer Ali Shah; Fariha Hasan; Safia Ahmed; Malik Badshah (BioEnergy Research, 2020)

Climate change impacts and adaptations for wheat employing multiple climate and crop modelsin Pakistan - Jamshad Hussain; Tasneem Khaliq; Senthold Asseng; Umer Saeed; Ashfaq Ahmad; Burhan Ahmad; Ishfaq Ahmad; Muhammad Fahad; Muhammad Awais; Asmat Ullah; Gerrit Hoogenboom (Climatic Change, 2020)

Correction to: Appraisal of disease-modifying potential of amlodipine as an anti-arthritic agent: new indication for an old drug - Sumera Qasim; Alamgeer; Saima Kalsoom; Muhammad Shahzad; Hafiz Muhammad Irfan; Muhammad Shoaib Zafar; Ishfaq Ali Bukhari; Fahim Vohra; Sibtain Afzal (Inflammopharmacology, 2020)

Appraisal of disease-modifying potential of amlodipine as an anti-arthritic agent: new indication for an old drug - Sumera Qasim; Alamgeer; Saima Kalsoom; Muhammad Shahzad; Hafiz Muhammad Irfan; Muhammad Shoaib Zafar; Ishfaq Ali Bukhari; Fahim Vohra; Sibtain Afzal (Inflammopharmacology, 2020)

Characterization of regional hydrological drought using improved precipitation records under multi-auxiliary information - Zulfiqar Ali; Ijaz Hussain; Muhammad Faisal; Marco Andreas Grzegorczyk; Ibrahim M. Almanjahie; Amna Nazeer; Ishfaq Ahmad (Theoretical and Applied Climatology, 2020)

Ammonia inhalation-induced inflammation and structural impairment in the bursa of fabricius and thymus of broilers through NF-κB signaling pathway - Syed Waqas Ali Shah; Muhammad Ishfaq; Muhammad Nasrullah; Abdul Qayum; Muhammad Usman Akhtar; Hyeonsoo Jo; Muhammad Hussain; Xiaohua Teng (Environmental Science and Pollution Research, 2020)

Use of crop growth model to simulate the impact of climate change on yield of various wheat cultivars under different agro-environmental conditions in Khyber Pakhtunkhwa, Pakistan - Farhana Gul; Ishfaq Ahmed; Muhammad Ashfaq; Dawood Jan; Shah Fahad; Xiuling Li; Depeng Wang; Muhammad Fahad; Muhammad Fayyaz; Syed Attaullah Shah (Arabian Journal of Geosciences, 2020)

Novel nonsense IL-12Rβ1 mutation associated with recurrent tuberculosis - Noor ul Akbar; Shahid Niaz Khan; Muhammad Usman Amin; Muhammad Ishfaq; Otavio Cabral-Marques; Lena F Schimke; Asif Iqbal; Ikram Ullah; Mubashir Hussain; Ijaz Ali; Nasar Khan; Nadia El Khawanky; et al. (Immunologic Research, 2019)

A framework to identify homogeneous drought characterization regions - Zulfiqar Ali; Ijaz Hussain; Muhammad Faisal; Alaa Mohamd Shoukry; Showkat Gani; Ishfaq Ahmad (Theoretical and Applied Climatology, 2019)

Inhibitory effects of Clematis orientalis aqueous ethanol extract and fractions on inflammatory markers in complete Freund's adjuvant-induced arthritis in Sprague–Dawley rats - Umme Habiba Hasan; Alamgeer; Muhammad Shahzad; Shah Jahan; Zahid Rasul Niazi; Ishfaq Ali Bukhari; Asaad Mohamed Assiri; Hamayun Riaz (Inflammopharmacology, 2019)

Estimation of Canal Water Deficit Using Satellite Remote Sensing and GIS: A Case Study in Lower Chenab Canal System - Muhammad Mohsin Waqas; Usman Khalid Awan; Muhammad Jehanzeb Masud Cheema; Ishfaq Ahmad; Matlob Ahmad; Sikandar Ali; Syed Hamid Hussain Shah; Allah Bakhsh; Muhammad Iqbal (Journal of the Indian Society of Remote Sensing, 2019)

Optimizing irrigation and nitrogen requirements for maize through empirical modeling in semi-arid environment - Ishfaq Ahmad; Syed Aftab Wajid; Ashfaq Ahmad; Muhammad Jehanzeb Masud Cheema; Jasmeet Judge (Environmental Science and Pollution Research, 2019)

Curcumin confers hepatoprotection against AFB1-induced toxicity via activating autophagy and ameliorating inflammation involving Nrf2/HO-1 signaling pathway - Ishfaq Muhammad; Xinghe Wang; Sihong Li; Rui Li; Xiuying Zhang (Molecular Biology Reports, 2018)

Protective role of curcumin in ameliorating AFB1-induced apoptosis via mitochondrial pathway in liver cells - Xinghe Wang; Ishfaq Muhammad; Xiaoqi Sun; Meiyu Han; Sattar Hamid; Xiuying Zhang (Molecular Biology Reports, 2018)

Yield Forecasting of Spring Maize Using Remote Sensing and Crop Modeling in Faisalabad-Punjab Pakistan - Ishfaq Ahmad; Umer Saeed; Muhammad Fahad; Asmat Ullah; M. Habib ur Rahman; Ashfaq Ahmad; Jasmeet Judge (Journal of the Indian Society of Remote Sensing, 2018)

Assessing the impact of climate variability on maize using simulation modeling under semi-arid environment of Punjab, Pakistan - Ishfaq Ahmed; Muhammad Habib ur Rahman; Shakeel Ahmed; Jamshad Hussain; Asmat Ullah; Jasmeet Judge (Environmental Science and Pollution Research, 2018)

Estimation of wind speed using regional frequency analysis based on linear‐moments - Muhammad Fawad; Ishfaq Ahmad; Falaq Ali Nadeem; Ting Yan; Aamar Abbas (International Journal of Climatology, 2018)
The quantiles of annual maximum wind speed (AMWS) can be estimated for different meteorological stations of interest by using at‐site frequency analysis and extreme value theory. These estimates are of immense importance for the codification of wind speed. However, the historical data of wind speed at the number of meteorological stations are sometimes unavailable and often insufficient due to the shorter length, especially in developing countries like Pakistan. The scarcity of the data increases the uncertainty of the quantiles estimates regarding policy implications. To cope with the problem, an approach of Regional Frequency Analysis (RFA) is opted here. In this study, RFA of AMWS using linear‐moments (L‐moments) is carried out by considering wind speed data of nine meteorological stations of province Punjab, Pakistan. No station is found to be discordant. A single homogenous region is constituted from these nine stations using a subjective approach based on their geographical locations. Heterogeneity measures justify that these nine stations of Punjab form a single homogeneous region. Regional quantiles estimates are found through the most appropriate probability distribution among generalized normal (GNO), generalized logistic (GLO), Pearson Type 3 (P3), generalized Pareto (GPA), Weibull (WEI), log Pearson Type 3 (LP3) and generalized extreme value (GEV) distributions. Z ‐statistic and L‐moment ratio diagram suggest that GLO and GNO distributions are better choices than others. Robustness of both distributions is evaluated through relative bias (RB) and relative root mean square error (RRMSE). Findings indicate that overall, GLO distribution is better than GNO. Further, we also find at‐site quantiles from dimensionless quantities (regional quantiles) using the sample mean and median as scaling factors. Quantiles' estimates calculated from this study can be used in codified structural designs for policy implications.

Evaluating the variability and trends in extreme climate events in the Kashmir Valley using PRECIS RCM simulations - Ishfaq Gujree; Ishfaq Wani; Muhammad Muslim; Majid Farooq; Gowhar Meraj (Modeling Earth Systems and Environment, 2017)

Effects of 2,4-dichlorophenoxyacetic acid combined to 6-Benzylaminopurine on callus induction, total phenolic and ascorbic acid production, and antioxidant activities in leaf tissue cultures of Crataegus azarolus L. var. aronia - Ghaya Chaâbani; Jessica Tabart; Claire Kevers; Jacques Dommes; Muhammad Ishfaq Khan; Sonia Zaoui; Lotfi Chebchoub; Mokhtar Lachaâl; Najoua Karray-Bouraoui (Acta Physiologiae Plantarum, 2015)

DNA methylation — an essential mechanism in plant molecular biology - Ishfaq Ahmed Hafiz; Muhammad Akbar Anjum; Abdul Ghaffar Grewal; Ghulam Ahmad Chaudhary (Acta Physiologiae Plantarum, 2001)